Implementation of Halal Supply Chain in the Cooperative of Islamic Boarding School: Maqashid Syariah Perspective - Siti Aminah Chaniago, Siti Aminah Chaniago; Muhammad Izza, Muhammad Izza; Bagaskara Sagita Wijaya, Bagaskara Sagita Wijaya; Feni Fitriani Putri Rozi, Feni Fitriani Putri Rozi (Jurnal Hukum Islam, 2024)
Halal Supply Chain is an opportunity, especially for countries with a majority Muslim population, including Indonesia, to increase the competitiveness of national products in a global context. Islamic boarding schools as centers for the development of Islamic law, also have the opportunity to create and apply Halal Supply Chain principles in the business units they develop. This research examines the application of Halal Supply Chain principles in Islamic boarding school cooperative business units that are integrated with Maqashid Syariah principles and their impact on business sustainability. This qualitative research was conducted at the "La Tansa" Retail Business Unit of Pondok Modern Darussalam Gontor. Data collection techniques used observation, interviews and document study. The research results show that implementing the Halal Supply Chain involves several steps to ensure that products and processes comply with the principles of Islamic law, such as (1) understanding halal requirements; (2) supplier selection; (3) production process; (4) halal certification; (5) documentation and tracking; (6) staff training; (7) storage and transportation; (8) regular audits and inspections; (9) continuous improvement. Implementation of the Halal Supply Chain in the "La Tansa" Retail Business Unit has integrated Maqashid Syariah principles. The implementation of Halal Supply Chain principles integrated with Maqashid Syariah principles contributes positively to the development of sustainable business models; and strengthen consumer confidence in the products and services offered.